2018
DOI: 10.5194/wes-3-767-2018
|View full text |Cite
|
Sign up to set email alerts
|

From wind to loads: wind turbine site-specific load estimation with surrogate models trained on high-fidelity load databases

Abstract: Abstract. We define and demonstrate a procedure for quick assessment of site-specific lifetime fatigue loads using simplified load mapping functions (surrogate models), trained by means of a database with high-fidelity load simulations. The performance of five surrogate models is assessed by comparing site-specific lifetime fatigue load predictions at 10 sites using an aeroelastic model of the DTU 10 MW reference wind turbine. The surrogate methods are polynomial chaos expansion, quadratic response surface, un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
95
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 42 publications
1
95
0
Order By: Relevance
“…Calibrating this function against higher fidelity simulations allows replacing the computationally expensive models with a quick and useful approximation. In Dimitrov et al, several wind turbine load surrogate model choices are compared, and the polynomial chaos expansion (PCE) is recommended as the potentially best choice out of the models considered. Further, in Schröder et al, ANNs are shown to match or exceed the performance of the PCE on a similar problem.…”
Section: Formulationmentioning
confidence: 98%
See 4 more Smart Citations
“…Calibrating this function against higher fidelity simulations allows replacing the computationally expensive models with a quick and useful approximation. In Dimitrov et al, several wind turbine load surrogate model choices are compared, and the polynomial chaos expansion (PCE) is recommended as the potentially best choice out of the models considered. Further, in Schröder et al, ANNs are shown to match or exceed the performance of the PCE on a similar problem.…”
Section: Formulationmentioning
confidence: 98%
“…For additional details regarding the calibration and use of PCE models, please refer to Sudret and also Murcia et al and Dimitrov et al for an example application to other wind energy‐related problems.…”
Section: Formulationmentioning
confidence: 99%
See 3 more Smart Citations